Re-Os systematics and chronology of graphite. (15th April 2022) - Toma, Jonathan; Creaser, Robert A.; Card, Colin; Stern, Richard A.; Chacko, Thomas; Steele-MacInnis, Matthew
Abstract: Natural graphite forms in a range of metamorphic and hydrothermal environments across timelines spanning from the birth of the solar system, to the evolution of early Precambrian life, and the development of contemporary geotectonic cycles. A precise timeline of these and other graphite-forming events, however, has hitherto been obscured by a lack of radiometric ages and as such, chronologies are inferred from host-rock or hydrothermal mineral ages. Herein we examine the Re-Os systematics and chronology of graphite formed in a suite of terrestrial and extraterrestrial environments (n = 17) with the principal aim of establishing the viability of Re-Os geochronology of natural graphite. Graphite Re and Os contents and isotopic ratios exhibit a wide range of values that extend up to 1520 ppb Re, 19, 577 ppt Os, and 4101 and 42.18 for 187 Re/ 188 Os and 187 Os/ 188 Os ratios, respectively. These values are broadly comparable to those reported for crustal sulfides, organic-rich sedimentary rocks, and hydrocarbons. X-ray diffraction crystallinity data reveals that graphite Re abundances show a broadly inverse correlation with graphite formation temperature and crystallinity (d002 and Lc(002) ) with interplanar spacing (d002 ) having the strongest anti-correlation with graphite Re contents. Graphite Re-Os geochronology is demonstrated with two independent case studies (Wollaston-Mudjatik Transition shear zones, Saskatchewan, Canada and Merelani Hills, Tanzania) yielding precise (<1%) Re-Os isochron dates of 1731.52 ± 7.43 Ma (2σ; MSWD = 1.3) and 586.89 ± 2.39 Ma (2σ; MSWD = 1.2) that are consistent, within uncertainty, to their mineralization ages constrained by other radiometric methods. These data confirm that graphite mineralization was synchronous with Trans-Hudsonian exhumation and tsavorite-tanzanite gemstone mineralization, respectively. Method accuracy, however, appears contingent on the analytical protocols used to isolate graphite, e.g. handpicking vs. heavy liquids (SPT) and water, with the latter perturbing graphite Re-Os systematics by as much as 20%. We, therefore, recommend handpicking paired with magnetic separation and grain mount examination. Our Re-Os age results are then coupled with new SIMS carbon isotope data (Wollaston-Mudjatik Transition graphite: δ 13 C = −21.64 to −15.28‰; Merelani Hills graphite: δ 13 C = −25.90 to −24.36‰) and 187 Os/ 188 Osi isotope data (Wollaston-Mudjatik Transition graphite = 0.3119 ± 0.0037; Merelani Hills graphite = 1.680 ± 0.038) to constrain graphitic carbon to sedimentary carbonate/organic (Wollaston-Mudjatik Transition graphite) and organic (Merelani Hills graphite) carbon sources. This unique pairing of isotope systems in graphite provides the first detailed chronology of localized carbon mobility in the Earth's crust. Re-Os graphite geochronology likely has wide applications in ore-deposit and metamorphic geology with the potential to reshape our understanding of carbon cycling in the crust-mantle system, and for graphite exploration initiatives that are critical for a global transition to a green economy.